2019
DOI: 10.1002/jcop.22272
|View full text |Cite
|
Sign up to set email alerts
|

Promoting resilience in street connected young people in Guatemala: The role of psychological and educational protective factors

Abstract: Street connected young people (SCYP) are at risk of encountering negative life experiences, such as abuse, neglect, violence and exploitation. Nonetheless, some demonstrate remarkable resilience. This study therefore aimed to explore protective factors that promote resilience in SCYP in Guatemala City. Using ethnographic interviews and image elicitation eight young people and four adult educational outreach project coordinators participated within this study. Three key protective factors emerged that help deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For example, Denkova et al found that offering short-term training in mindfulness improved markers of resilience in firefighters (Denkova et al, 2020). Furthermore, some research has suggested that feelings of empowerment and of belonging may help to promote resilience (Oldfield et al, 2020). These may be particularly important to consider in light of the aforementioned changes to annual leave and rotas.…”
mentioning
confidence: 99%
“…For example, Denkova et al found that offering short-term training in mindfulness improved markers of resilience in firefighters (Denkova et al, 2020). Furthermore, some research has suggested that feelings of empowerment and of belonging may help to promote resilience (Oldfield et al, 2020). These may be particularly important to consider in light of the aforementioned changes to annual leave and rotas.…”
mentioning
confidence: 99%
“…For example, a study from Guatemala city points that three key protective factors can help develop resilience in young people living in the street situation; the first is the empowerment, with educational projects support, providing opportunities; the second is the belongingness, creating positive relationships, a sense of affinity, and positive family environments; and the third is the motivation which highlights the importance of the young peoples’ willpower, engagement with learning, and help‐seeking behavior (Oldfield, Stevenson, & Ortiz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…willpower, engagement with learning, and help-seeking behavior (Oldfield, Stevenson, & Ortiz, 2019).…”
Section: Multigroup Semmentioning
confidence: 99%
“…For example, Denkova et al (2020) found that offering short-term training in mindfulness improved markers of resilience in firefighters. Some research has suggested that feelings of empowerment and belonging may help to promote resilience (Oldfield et al, 2020). Through OAEE programs, curriculum is often developed to help students learn how to successfully deal with adversity and enhance personal resilience, through a process of engaging and increasingly difficult and more complex challenges, structured facilitation, and reflection, which allows students to see their greater potential for dealing with future challenging and adverse situations (e.g., resilience).…”
Section: Resiliencementioning
confidence: 99%